Implementasi Kurikulum Merdeka Dalam Pembentukan Karakter Siswa SD Al-Madina Wonosobo - Ima Rahmatika, Aza; Majid, Abdul; Fatiatun (Universitas Majalengka, 2023)
In this research, the author aims to investigate the implementation of the Merdeka Curriculum in forming the character of Al-Madinah Elementary School students, Wonosobo. This research uses a qualitative approach with a case study design. Data was collected through classroom observations, interviews with teachers and students, as well as document analysis related to the implementation of the Independent Curriculum. The study findings show that the independent learning curriculum has been implemented at the Al-Madinah Wonosobo Elementary School, but teachers experienced several obstacles in implementing it. Obstacles related to understanding revolve around a lack of understanding of the concept of